Considerations of circadian impact for defining 'shift work' in cancer studies: IARC Working Group Report. Issue 2 (20th October 2010) - Stevens, Richard G; Hansen, Johnni; Costa, Giovanni; Haus, Erhard; Kauppinen, Timo; Aronson, Kristan J; Castaño-Vinyals, Gemma; Davis, Scott; Frings-Dresen, Monique H W; Fritschi, Lin; Kogevinas, Manolis; Kogi, Kazutaka; et al.
Abstract : Based on the idea that electric light at night might account for a portion of the high and rising risk of breast cancer worldwide, it was predicted long ago that women working a non-day shift would be at higher risk compared with day-working women. This hypothesis has been extended more recently to prostate cancer. On the basis of limited human evidence and sufficient evidence in experimental animals, in 2007 the International Agency for Research on Cancer (IARC) classified 'shift work that involves circadian disruption' as a probable human carcinogen, group 2A. A limitation of the epidemiological studies carried out to date is in the definition of 'shift work.' IARC convened a workshop in April 2009 to consider how 'shift work' should be assessed and what domains of occupational history need to be quantified for more valid studies of shift work and cancer in the future. The working group identified several major domains of non-day shifts and shift schedules that should be captured in future studies: (1) shift system (start time of shift, number of hours per day, rotating or permanent, speed and direction of a rotating system, regular or irregular); (2) years on a particular non-day shift schedule (and cumulative exposure to the shift system over the subject's working life); and (3) shift intensity (time off between successive work days on the shift schedule). The group also recognised that for further domains to be identified, more research needs to be conducted on the impact of various shift schedules and routines on physiological and circadian rhythms of workers in real-world environments.